Clinical Investigation on the Impact of Cannabis Abuse on Thyroid Hormones and Associated Psychiatric Manifestations in the Male Population - Muzaffar, Anum; Ullah, Sami; Subhan, Fazal; Nazar, Zahid; Hussain, Syed Mehdi; Khuda, Fazli; Khan, Abuzar; Khusro, Ameer; Sahibzada, Muhammad Umar Khayam; Albogami, Sarah; El-Shehawi, Ahmed M.; Emran, Talha Bin; et al. (Frontiers in Psychiatry, 2021)
Abstract Cannabis abuse is a common public health problem and may lead to considerable adverse effects. Besides others, the development of dependence on cannabis consumption has significant consequences on biochemical and clinical symptoms. This study was designed to evaluate the effects of harmful use of cannabis on thyroid hormonal levels, cardiovascular indicators, and psychotic symptoms in patients against positive control subjects. This prospective multicenter study was conducted on cannabis-dependent patients with psychotic symptoms (n=40) versus positive control subjects (n=40). All participants were evaluated for psychiatric, biochemical, and cardiovascular physiological effects. Patients were selected utilizing DSM-IV criteria and urine samples, exclusively for cannabis presence. Serum TSH, T3, and T4 levels were measured using the immunoassay technique. Patients were assessed for severity of depressive, schizophrenic, and manic symptoms using international ranking scales. Various quantifiable factors were also measured for tolerance development. Among cannabis abused patients, 47.5% were found with schizophrenia, 20% with schizoaffective, 10% with manic and, 22.5% with both manic and psychotic symptoms. Upon group-group and within-group statistical analysis, results of thyroid hormones and cardiovascular parameters were non-significant. The psychiatric assessment showed highly significant (P < 0.001) exacerbation of positive, negative, general psychopathology, and total scores (through PANSS rating scales) in patients versus the positive control subjects. The study revealed that cannabis abuse did not significantly alter thyroid hormones and cardiovascular parameters due to tolerance development. However, the patients showed a significant increase in positive, negative, and manic symptoms in different psychiatric disorders due to cannabis abuse than positive control subjects.